The COVID-19 Virus Wears Stiletto: Review of Gendered Socio-economic Impacts and Implications of the Corona virus Pandemic on Women and Girls in Zimbabwe - Chigiya-Mujeni, Ruvarashe (Quest Journal of Management and Social Sciences, 2020)
Background: With its ability to mutate and take charge of its hosts’ respiratory organs, COVID-19 has ravaged the global north and south alike. The world’s greatest economies are crumbling and death tolls continue to rise exponentially. The most recent strain of the coronavirus has spread like wildfire, sparing neither the rich nor the poor. It is pertinent, however, to note that natural disasters do not affect members of society unilaterally. Women, children and the disabled interact with global and national disasters differently, highlighting the urgent need to take cognizance of the various elements that constitute the measures drafted and implemented to tackle the spread and impact of these disasters. Objective:This paper seeks to demonstrate these intricacies based on the webinar seminar held in March 2020 by UN Women in Zimbabwe and discuss the impact and implications of this virus on women and girls in Zimbabwe and bring out the challenges faced as they fight the virus in various socioeconomic settings Methods: A desk review approach was used to highlight the various gender dimensions surrounding the coronavirus and its implications on women and girls in Zimbabwe. Results: Women, due to their multiple roles and biological makeup, are more vulnerable to succumb to this disease and besides their biological disposition women are impacted differently and negatively by the pandemic. Conclusions: There is a need to take a holistic approach in dealing with issues of the pandemic without ignoring the fact that women are on the receiving end. Implications: This paper is useful to policy makers, institutions working on COVID-19 and government to take necessary actions. Originality: This paper is original and not sent anywhere else for the publication.